Answer:
b : a = 1 : 4
Step-by-step explanation:
<em>
=
</em>
<em>3 ( a + b) = 5 ( a - b)</em>
<em>3 a + 3 b = 5 a - 5 b</em>
<em>5 b + 3 b = 5 a - 3 a</em>
<em>8 b = 2 a</em>
<em>
=
</em>
b : a = 1 : 4
Answer:
D) The function is always decreasing
Step-by-step explanation:
As you move along the x axis, the x value approaches: a) negative infinity when x < 0 and b) 0 when x > 0
Answer:
y=4
Step-by-step explanation:
3(9) +4y= 43
27+4y=43
4y=16
y=4
Answer: what??
Step-by-step explanation:
Hi there!
There are multiple solutions to your question. Some possible solutions could be the following:
(0, -5)
(1, 0)
(2, 5)